If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4r + -2)(5r + 2) = 0 Reorder the terms: (-2 + 4r)(5r + 2) = 0 Reorder the terms: (-2 + 4r)(2 + 5r) = 0 Multiply (-2 + 4r) * (2 + 5r) (-2(2 + 5r) + 4r * (2 + 5r)) = 0 ((2 * -2 + 5r * -2) + 4r * (2 + 5r)) = 0 ((-4 + -10r) + 4r * (2 + 5r)) = 0 (-4 + -10r + (2 * 4r + 5r * 4r)) = 0 (-4 + -10r + (8r + 20r2)) = 0 Combine like terms: -10r + 8r = -2r (-4 + -2r + 20r2) = 0 Solving -4 + -2r + 20r2 = 0 Solving for variable 'r'. Factor out the Greatest Common Factor (GCF), '2'. 2(-2 + -1r + 10r2) = 0 Factor a trinomial. 2((-2 + -5r)(1 + -2r)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + -5r)' equal to zero and attempt to solve: Simplifying -2 + -5r = 0 Solving -2 + -5r = 0 Move all terms containing r to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -5r = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -5r = 0 + 2 -5r = 0 + 2 Combine like terms: 0 + 2 = 2 -5r = 2 Divide each side by '-5'. r = -0.4 Simplifying r = -0.4Subproblem 2
Set the factor '(1 + -2r)' equal to zero and attempt to solve: Simplifying 1 + -2r = 0 Solving 1 + -2r = 0 Move all terms containing r to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2r = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2r = 0 + -1 -2r = 0 + -1 Combine like terms: 0 + -1 = -1 -2r = -1 Divide each side by '-2'. r = 0.5 Simplifying r = 0.5Solution
r = {-0.4, 0.5}
| x=3y-18 | | 7b^2=602 | | 3/2=6/x | | 3x-6y=48 | | 3/2=-4/a | | 7-3x+1=2(x-1) | | 1/6x+3(1/9x-4)=5 | | a/3=333 | | s=a-dfora | | 1/3m=24 | | 56x^2-15x=56x | | 3.03+30.3=60.6 | | r/-56=156 | | 1/3(9x-3)=-3 | | 3/4x-5/4=10 | | 20=-3(3a-2) | | 2.47x+16=6.1009+4x | | 5.9x+5.2x=199.8 | | 2+5x-5=3(x-2) | | 7w-4+1w+12=0 | | (-5w/4)-2=-8w+8 | | -8=-4x+4 | | 3(x-1)+7=3x+1 | | 6y-6(-y)=0 | | -4-2x-8=3x-7 | | 30=-5k | | 10x+2y=360 | | -144=-8n | | 9/p+3/8-2/5=7 | | -7s=-105 | | 5x(x+3)+(x^3+27)=0 | | 2/3-3z/4+1/2=-1/3 |